2021
DOI: 10.1101/2021.01.26.428210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsupervised discovery of dynamic cell phenotypic states from transmitted light movies

Abstract: SummaryIdentification of cell phenotypic states within heterogeneous populations, along with elucidation of their switching dynamics, is a central challenge in modern biology. Conventional single-cell analysis methods typically provide only indirect, static phenotypic readouts. Transmitted light images, on the other hand, provide direct morphological readouts and can be acquired over time to provide a rich data source for dynamic cell phenotypic state identification. Here, we describe an end-to-end deep learni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Taken together, methods such as DeepIFC able to perform virtual labeling and cell type identification solely from morphology hold promise to transform diagnosis of hematological diseases and blood processing pipelines by not having to introduce fluorescent labels during workflow, reducing costs and processing time required. Possible avenues to develop the method further include utilizing larger training datasets covering more cell types, data augmentation to improve performance on rare cell types (Luo, Nguyen et al . 2021), and a user-friendly graphical tool to use the software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, methods such as DeepIFC able to perform virtual labeling and cell type identification solely from morphology hold promise to transform diagnosis of hematological diseases and blood processing pipelines by not having to introduce fluorescent labels during workflow, reducing costs and processing time required. Possible avenues to develop the method further include utilizing larger training datasets covering more cell types, data augmentation to improve performance on rare cell types (Luo, Nguyen et al . 2021), and a user-friendly graphical tool to use the software.…”
Section: Discussionmentioning
confidence: 99%
“…Label-free deep learning methods have been created to reconstruct fluorescent images from brightfield images (Christiansen et al 2018, Ounkomol et al 2018, Nguyen et al 2021), but to our knowledge, the reconstruction of single-cell multichannel fluorescent images in IFC data has not been proposed. Label-free cytometry methods based on segmentation and unsupervised modeling (Nguyen et al 2021), weak supervision (Otesteanu et al 2021), cytometry by time of flight (CyTOF) (Hu et al 2020) and time-stretch microscopy (Li et al 2019) have been suggested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3; Fig. S3; see Methods) 27 . Using this method, we tracked a total of 120 clonal lineages over 4 days and an average of 4.4 cell generations.…”
Section: The Early Effector and Memory Decision Occurs Heterogeneousl...mentioning
confidence: 99%
“…S3A-B), modified to enable segmentation of cells from brightfield movies. Importantly, to segment cells without additional fluorescent labels besides Tcf7-YFP, we first trained a convolutional neural network (CNN) with a U-net architecture 61 to predict fluorescence images of whole cells from brightfield images, using images of cell-trace violet labeled T cells as a training data set 27 . We trained separate CNNs for the images acquired in 96-well plates (Fig.…”
Section: Image Segmentation and Trackingmentioning
confidence: 99%